Establishing exclusive breastfeeding among in-patient malnourished infants in a rural Kenyan hospital: mothers' experiences of a peer supporter intervention - Kahindi, J; Jones, C; Berkley, JA; Mwangome, M (BioMed Central, 2020)
Background: The 2013 WHO guidelines for nutritional rehabilitation of hospitalized and non-hospitalized malnourished infants under six months (u6m) recommend the re-establishment of exclusive breastfeeding. However, in most low-income settings these recommendations are not consistently applied. A recently concluded pilot study on the effects of implementing these guidelines among hospitalized malnourished infants u6m of age in Kilifi, Kenya introduced breastfeeding peer supporters (BFPS) to the inpatient setting to support guideline implementation. Here we report a sub-study investigating mothers’ experiences and perceptions of the process of re-establishing exclusive breastfeeding during their infant’s admission to hospital.